Alevism in politics: Possibilities and limits of Alevi identity politics - Ertan, Mehmet. (Thesis (Ph.D.) - Bogazici University. Atatürk Institute for Modern Turkish History, 2016., 2016)
This dissertation scrutinizes the politicization of Alevism in the 1990s. The politicization of Alevi identity as the basis of a socio-political movement is shaped by culturel turn of politics stemming from debates on postmodernism, multiculturalism and globalization,,but the Alevi movement has never been a classical identity movement. Its ambivalent characteristics, which derive from a heterodox cosmology, ethnic pluralism, and geographical distribution, makes Alevism’s availability as a defining component of identity movement difficult. Despite this ambivalence, historical massacres provide Alevi identity with a stable foundation. The ambivalence of Alevi identity and fear of new massacres shape the dynamism of its politicization. In this regard, the Alevi movement, which politicizes without direct reference to Alevi identity, focuses on universal ideologies that provide for equal coexistence of Alevis and non-Alevis. Citizenship and secularism have thus become key concepts of the Alevi movement. Aer analysis of the structural framework of Alevi politicization, this dis-sertation examines its dynamism of Alevism through the main agents of the movement in the 1990s: Alevi associations and the Peace Party. Various defi-nitions and historiographies of Alevism developed by these associations as well as their differentiated positions toward political parties and state struc-tures demonstrate the contested associational domain of Alevi politics. At an-other level, discussions during the formation of the Peace Party and its subse-quent failure demonstrate the difficulty of using Alevism as an ideological source for a party. us, this dissertation underscores the multidimensional relation between culture and politics.
Keywords: Alevism.; Alevis -- Political activity -- Turkey.; Alevis -- Political aspects -- Turkey.